Relationship Between Anemia and Telogen Effluvium in Post-COVID-19 Survivors - Canan Emiroglu; Murat Dicle; Suleyman Gorpelioglu; Cenk Aypak (Dermatology Practical & Conceptual)
Introduction: There are insufficient studies in the literature on the relationship between the acute severity of the disease and the occurrence of anemia and telogen effluvium (TE) in the post-coronavirus disease 2019 (COVID-19) period.